Defluoridation of drinking water using pural (R) MG-20 mixed hydroxide adsorbent - Patankar, Gaurang V.; Tambe, Amruta S.; Kulkarni, Bhaskar D.; Malyshew, Alexander; Kamble, Sanjay P. (Water Air and Soil Pollution, 2013)
The potential ofmixed alumina-magnesia hydroxide adsorbent (PURAL (R) MG-20) for defluoridation of drinking water using batch and continuous mode of operations has been reported in the present article. Systematic adsorption experiments were carried out to elucidate the effects of different process parameters such as adsorbent dose, initial fluoride concentration, pH of the solution and effect of other ions (usually present in groundwater). These studies were aimed to understand the adsorption behaviour of the PURAL (R) MG-20 adsorbents. Fluoride adsorption by PURAL (R) MG-20 sorbent was found pH dependent. Maximum fluoride removal efficiency was observed in the range of pH 5-7. Langmuir isotherm described the data better than Freundlich and Temkin isotherm models and the adsorption capacity was found to be 5.62 mg g(-1) at initial fluoride concentration of 5.13 mg L-1, pH 7 and contact time 24 h. The kinetic result shows that the fluoride sorption follows pseudo-second-order kinetics. Column breakthrough studies were performed to test the performance of the adsorbent media at continuous mode of operation. Thus, it can be concluded that PURAL (R) MG-20 adsorbent can be used directly for field applications since it shows high fluoride uptake capacity under simulated drinking water conditions and it is also commercially available.
Keywords: Breakthrough studies; Defluoridation of drinking water; Kinetic modelling; Mixed hydroxide adsorbent